2011
DOI: 10.1002/aqc.1191
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, abundance, and movements of the bottlenose dolphin (Tursiops truncatus) in the Pelagos Sanctuary MPA (north-west Mediterranean Sea)

Abstract: ABSTRACT1. The Pelagos Sanctuary is the largest marine protected area of the Mediterranean Sea (87 500 km 2 ), and is located in the north-west part of the basin. The presence of the bottlenose dolphin in this area is well documented but its distribution and abundance are not well known.2. The present study collected and analysed data from 10 different research groups operating in the Pelagos Sanctuary from 1994 to 2007. Photo-identification data were used to analyse the displacement behaviour of the dolphins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 32 publications
5
76
2
Order By: Relevance
“…It was only around the Tuscan Archipelago, eastern Corsica and in the Ligurian Sea that coastal waters were used throughout the year. This contrast in seasonal distribution has, to our knowledge, never been described in the NWMS, since the bottlenose dolphin is considered inhabiting mainly continental shelves: previous studies reported bottlenose dolphins to be present only over the shelf, within the 200 m isobath [29,33]. In contrast, we showed here that, even in summer, bottlenose dolphins were also frequent in offshore waters up to 1,000 m deep.…”
Section: Ecological Preferencescontrasting
confidence: 70%
“…It was only around the Tuscan Archipelago, eastern Corsica and in the Ligurian Sea that coastal waters were used throughout the year. This contrast in seasonal distribution has, to our knowledge, never been described in the NWMS, since the bottlenose dolphin is considered inhabiting mainly continental shelves: previous studies reported bottlenose dolphins to be present only over the shelf, within the 200 m isobath [29,33]. In contrast, we showed here that, even in summer, bottlenose dolphins were also frequent in offshore waters up to 1,000 m deep.…”
Section: Ecological Preferencescontrasting
confidence: 70%
“…; Gnone et al . ). According to mark–recapture studies, resident coastal population sizes were likely to be around 600–800 individuals for each of the two populations (M. Louis, unpublished data for the Normandy resident group, López ; Pesante et al .…”
Section: Discussionmentioning
confidence: 97%
“…Some coastal groups are resident but movements were reported between Corsica and France (Gnone et al . ), indicating that individuals crossed pelagic waters. The pelagic habitat use was confirmed by aerial surveys conducted during winter where bottlenose dolphins were mainly sighted in deep‐water (>200 m) areas (SAMM, 2011/2012, E. Pettex, personal communication).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there is no Mediterranean-wide abundance estimate for bottlenose dolphins. The only large scale studies were focused in the NW Mediterranean Sea (Forcada et al, 2004;Gnone et al, 2011;Lauriano et al, 2014) and found an overall low density of bottlenose dolphins, with animals rarely found in pelagic waters. Most groups occurred in coastal areas of the main insular systems, the Balearic Islands, Corsica, Sardinia, and around small islands near the continent.…”
Section: Introductionmentioning
confidence: 99%